Labor Market Reforms and Current Account Imbalances: Beggar-Thy-Neighbor Policies in a Currency Union? - Timo Baas; Ansgar Belke (Institute for the Study of Labor (IZA), 2014)
Member countries of the European Monetary Union (EMU) initiated wide-ranging labor market reforms in the last decade. This process is ongoing as countries that are faced with serious labor market imbalances perceive reforms as the fastest way to restore competitiveness within a currency union. This fosters fears among observers about a beggar-thy-neighbor policy that leaves non-reforming countries with a loss in competitiveness and an increase in foreign debt. Using a two-country, two-sector search and matching DSGE model, we analyze the impact of labor market reforms on the transmission of macroeconomic shocks in both, non-reforming and reforming countries. By analyzing the impact of reforms on foreign debt, we contribute to the debate on whether labor market reforms increase or reduce current account imbalances.
Keywords: E24; E32; J64; F32; 330; current account deficit; labor market reforms; DSGE models; search and matching labor market